Hubungan customer engagement melalui Instagram @perpustakaandikbud dengan minat kunjungan perpustakaan di kalangan follower aktif - Rachmi Anindyaputri; Agus Rusmana; Neneng Komariah (Universitas Padjadjaran, 2020)
The internet in the business world have led to new promotion forms using social media known as customer engagement, a series of activities carried out by social media users to engage with brands or organizations. The Ministry of Education and Culture’s Library via Instagram @perpustakaandikbud as institutions that provide information services used social media in their promotional activities. This study aimed to determine the customer engagement’s correlation through Instagram @perpustakaandikbud with interest in visiting the library among active followers. This study used quantitative methods with a correlational approach with the research sample was 83 respondents, obtained by using a simple random sampling technique. The researchers were collected research data using questionnaires, interviews, and literature studies. The inferential correlation test used a simple linear regression analysis using the product-moment formula. Results showed that customer engagement, based on the indicators of absorption, dedication, vigor, and interaction, had a significant relationship with interest in visiting the library. This was proven by testing the major hypothesis; namely, the calculation results obtained a correlation coefficient of 0.521. It obtained a tcount of 4,417 and ttable of 1,663. The tcount was more significant than the ttable, so the hypothesis was accepted. Customer engagement through Instagram @ perpustakaandikbud correlated with the followers’ interest in visiting the Ministry of Education and Culture’s Library. This research concludes that Instagram social media is an effective library promotion media in increasing user's interest.